A hidden function of US secondary sanctions: blocking the right to development - Strauss, Michael J. (Journal of the Belarusian State University. International Relations, 2025)
This article strengthens existing arguments that US secondary sanctions violate international law. It proposes that they constitute a restrictive business practice that obstructs the right to development. Such sanctions penalise trade and competition that economists consider essential for development. By deterring foreign companies from doing business with states or major economic actors targeted by US primary sanctions, secondary sanctions effectively reserve the target’s market for US companies once sanctions are lifted. Secondary sanctions, operating internationally, meet the definition of restrictive business practices that the UN Conference on trade and development has sought to curtail domestically. It may therefore offer a mechanism for challenging them on such grounds.